Students’ Mathematical Connection Ability on Quadratic Function with Realistic Mathematics Education (RME) Approach - Ardhina Wijayanti; Ibrahim Ibrahim (Southeast Asian Mathematics Education Journal, 2025)
Students need to be able to make mathematical connections because it helps them learn math more thoroughly, retain it longer, and help solve problems. This study aimed to determine whether RME learning can improve students' mathematical connection skills. This type of research is experimental research with a nonequivalent control group design. This study used two groups as test subjects, each with 32 students, selected through a cluster random sampling technique. The data collection instrument used in this research is the mathematical connection ability test. The data analysis techniques used were an Independent Sample T-test, an effect size test, test results of each indicator of mathematical connection ability, and daily journal notes. The results showed that students who learned RME learning were more proficient in making mathematical connections than those who learned using conventional learning. In addition, the experimental group students experienced increased self-confidence and courage to express their ideas and see the surrounding events as part of the mathematical concepts they had learned.